2022
DOI: 10.1128/spectrum.00506-22
|View full text |Cite
|
Sign up to set email alerts
|

Genome of Malassezia arunalokei and Its Distribution on Facial Skin

Abstract: Malassezia is the fungus predominantly residing on the human skin and causes various skin diseases, including seborrheic dermatitis and dandruff. To date, 18 species have been reported, and among them, M. restricta is the most predominant on human skin, especially on the scalp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…During life, the skin mycobiome could vary across body site localization or hygiene as shown by culture-dependent and independent methods [ 19 , 128 , 129 , 130 ]. Sebaceous body sites (e.g., face, chest and back) had a higher fungal diversity of lipophilic species compared to moist or dry skin sites [ 120 , 128 ].…”
Section: Skin Mycobiomementioning
confidence: 99%
See 1 more Smart Citation
“…During life, the skin mycobiome could vary across body site localization or hygiene as shown by culture-dependent and independent methods [ 19 , 128 , 129 , 130 ]. Sebaceous body sites (e.g., face, chest and back) had a higher fungal diversity of lipophilic species compared to moist or dry skin sites [ 120 , 128 ].…”
Section: Skin Mycobiomementioning
confidence: 99%
“…Site specification is typical for Malassezia : the higher abundance of M. globosa on the scalp and forehead and lower abundance on the back were observed, while the relative abundance of M. sympodialis showed an inverse pattern [ 123 ]. Malassezia arunalokei was more abundant on the forehead and cheek compared to the scalp [ 129 ]. Seasonal and gender-related changes in the skin mycobiome were observed [ 131 , 132 ].…”
Section: Skin Mycobiomementioning
confidence: 99%
“…Fluconazole diffusion was retained, but no difference in susceptibility of C. albicans to the drug was observed in polymicrobial biofilms [5]. A direct influence of secreted enzymes, such as proteinase, from the major skinassociated fungus Malassezia on the biofilm formation of Staphylococcus aureus, a noteworthy skin opportunistic bacterial pathogen, was also demonstrated experimentally [6].Malassezia is a commensal fungus found on the skin surfaces of warm-blooded animals, including humans, and comprised of 18 species [7][8][9]. Several studies based on amplicon sequencing and metagenome analysis demonstrated that Malassezia is the most dominant genus in the human skin.…”
mentioning
confidence: 97%
“…Malassezia is a commensal fungus found on the skin surfaces of warm-blooded animals, including humans, and comprised of 18 species [7][8][9]. Several studies based on amplicon sequencing and metagenome analysis demonstrated that Malassezia is the most dominant genus in the human skin.…”
mentioning
confidence: 99%
“…2016, M. arunalokei was recognized as a new species. It was isolated from scalp skin of a human patient with seborrheic dermatitis in Chandigarh in India in Defrom this species 7.1 million years ago[13,24].In 2018, new species, M. vespertilionis, was isolated from bats in the eastern and western states of the USA.…”
mentioning
confidence: 99%